Feasibility study on the homogeneity and stability of megastigmatrienone isomers for the development of certified reference material - Kim, Mi Jung; Kim, Minyeong; Kim, Sangseop; Lee, Kyungjin; Kim, Yongjune; Kim, Joon; Yoon, Tae Jong; Kim, Hyoungsu; Baek, Seung Hoon (Journal of Food Composition and Analysis, 2023)
Megastigmatrienone is a natural flavoring food additive with a spicy and tobacco-like aroma. A feasibility study on the homogeneity and stability of megastigmatrienone preceded for the development of a certified reference material (CRM). Megastigmatrienone, a mixture of four diastereomers, was prepared using gram-scale synthesis. The purity values of candidate megastigmatrienone reference material (MRM) determined using two independent methods showed comparable results by GC–MS assay (90.89%) and mass balance method (92.42%). Candidate MRM aliquoted into vials was confirmed to be homogenous between the bottles. In the stability test, various packaging methods and environmental conditions capable of stabilizing megastigmatrienone were tested. Candidate MRM aliquoted into vials was unstable from –20 °C to 40 °C for 12 months. However, either antioxidant additive or argon-substituted heat-sealing package significantly improved its stability. These findings suggest that atmospheric reactive radicals may be critical factors resulting in the decomposition of megastigmatrienone. Argon-substituted packaging and storage temperatures below −20 °C are the practical alternatives to sustain its stability. This study systematically demonstrates strategies for stabilizing materials with poor stability. Our findings can be useful for developing megastigmatrienone CRM to guarantee the reliable quality of food additives or foods containing megastigmatrienone.
Keywords: GC–MS; Homogeneity; Megastigmatrienone; Reference material; Stability; Tabanone